Model Desain Pembelajaran Berbasis Teologi Dan Misi Pengabaran Injil: Pengaruhnya Terhadap Minat Belajar Peserta Didik - Delpi Novianti; Sri Rezeki (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Christian education is aimed at forming an individual who is integral and strong in the Christian faith. One key approach to achieving this goal is through a learning design that is rooted in Christian theological principles and the mission of evangelism. This learning design emphasizes the understanding and application of Christian values in everyday life. Interest in learning is an important factor that influences the learning outcomes of the students. Interesting learning designs that match the interests of the learners can increase their interest in the learning process. Therefore, it is important to evaluate the influence of the use of theological-based learning design models and the mission of evangelism on the learning interests of learners. The study uses descriptive qualitative methods to analyze data from a variety of sources of information. The results show that theological-based learning design models and evangelization missions can enhance the interest of students in learning. This is due to a number of factors, among others: This learning model focuses on Christian values that are relevant to the daily life of the student. The learning model involves the student actively in the learning process. It provides an opportunity for the student to apply Christian value in everyday life. This research has important relevance in an effort to improve the understanding and application of the theological-based learning design models and the mission of evangelism. This model of learning can help the student understand, internalize, and apply Christians values in daily life, as well as prepare them to play an active role in evangelization.